Role of Residency Interview Preparatory Activities as a Determinant on Pharmacy Residency Match Rates. (April 2017) - Caballero, Joshua; Benavides, Sandra; Clauson, Kevin A.; Hardigan, Patrick C.; Steinberg, Jennifer G.; Gauthier, Timothy P.; Sherman, Elizabeth M.; Seamon, Matthew J.; Valdes, Jose; Thomas, Jennifer E.
Purpose: Different strategies have been implemented to assist students in securing residency positions. The purpose of this study was to explore the impact of student participation in residency preparation activities on match rates. Methods: A retrospective observational study was conducted to explore the effect of participation in residency preparation activities and grade point average (GPA) on residency match rate. Match rates for students participating in the Residency Interview Preparation Seminar (RIPS) or mock interviews (ie, intervention group) were compared with students who participated in neither activity (ie, control group). Results: A total of 118 individuals were included in the comparison. Forty-eight students participated in RIPS (n = 29) or mock interviews (n = 19), while 70 students were in the control group. The intervention group had a statistically larger proportion of students securing residency than the control group (81% vs 57%; P = .009). Match rates between students enrolled in RIPS versus those in the mock interview group were not significant. No statistically significant differences were observed based on GPA. Conclusion: Students receiving additional preparation prior to interviews when seeking postdoctoral training were significantly more likely to obtain a residency position. In academic settings with limited resources, mock interviews may be preferred over comprehensive preparatory courses.